The Quality of life and perceived health education needs of type 2 diabetic clients in Negros Oriental, Philippines - Abalos, Evalyn E.; Gloria, Grace A.; Obate, Michael B.; Bustamante, Veveca V.; Campoy, Marnesa P. (2013)
This paper examines the factors influencing the quality of life (QoL) of Type 2 Diabetes Mellitus clients and their perceived health education needs. The 55 respondents of the study were recruited through convenience sampling from four diabetes clinics in Dumaguete City, Negros Oriental. The Ferrans and Powers Quality of Life Index (QLI) was administered, a test that has four subscales, namely: [1] health and functioning, [2] social and economic, [3] psychological/spiritual, and [4] family subscales. The subscale scores and the overall QoL score were then correlated with the profile of the respondents. The results showed no significant relationship between the socio-demographic profile and the overall QoL score, but only between individual QoL subscales such as educational level and the social and economic subscale, monthly family income and the social and economic subscale, and monthly family income and family subscale. The health topics they reportedly needed include blood sugar monitoring, diet, exercise and medications. Meanwhile, a health education program based on the specified needs should be developed and integrated into the curriculum of nursing students.